EFFECT OF FEEDING VETCH SEEDS (Vicia sativa L.), AS SOURCE OF PROTEIN IN FATTENING RATIONS OF AWASSI LAMBS - M. M. Kassem (Mesopotamia Journal of Agriculture, 2007)
Thirty five Awassi lambs of 5.5–6 months old, with average initial body weight 34.25 kg were divided randomly into five groups each of 7 lambs. All lambs groups were fed ad libitum for 70 days on one of the five rations. The first group (A) was fed on barley grain only, group (B) barley grain with 10% sun flower meal and 0.7% urea, group (C) barley grain with 10% vetch seeds, group (D) barley grain with 20% vetch seeds and finally group (E) barley grain with 30% vetch seeds in addition to limestone and salt. After 4 weeks four lambs were randomly chosen from each group for digestibility trials to study the effects of treatments on nutrients digestibility. At the end of the experiment three lambs from each group were randomly chosen and slaughtered to study the carcass characteristics. Daily food intake for the five groups were similar and there was no significant differences in the digestibility of DM, CP, ether extract and CF. whereas the group that took 30% vetch seeds had a significantly higher NFE digestibility compared with group A. calculated increases were observed in feed conversion efficiency, average daily gain, final weight, carcass weight, dressing percentage, rib eye area and fat thickness for group (E).